Potential of Elemental Sulfur Fertigation to Reduce High Soil pH for Production of Highbush Blueberry - Machado, RMA (2012)
Abstract Blueberry is adapted to acidic soil conditions but is often planted in high pH soils by adding elemental sulfur (So) prior to planting. Two pot experiments were carried out in a glasshouse to determine the potential of applying Sº by fertigation through a drip irrigation system. In the first experiment, So was applied at four rates of 0, 0.36, 0.72, and 1.44 g per application to 4-L pots filled with one of three different soil textures [1:0, 1:1, and 1:2 sandy loam soil:sand (v/v)]. In the second experiment, So was applied at three rates of 0, 0.36, 0.72 g per application to 4- and 16-L pots filled with soil only. Pots were irrigated using a 2.3 L•h-1 pressure-compensating drip emitter located in the center of each pot. Micronized water-dispersible Sº granules were dissolved in water and injected through the drip system twice a week for 4 weeks in each experiment. Soil leachate pH decreased from 6.5 to 4.2 within 19 days after So was first applied in the first experiment, but pH was not affected by soil texture or the amount of So applied and decreased only 0.2 units by additional So applications made between 19 and 33 days. Soil and soil leachate pH likewise decreased from 7.3 to 4.5 in the second experiment, but in this case, pH took up to 10 days longer to decline in the 14-L pots than in the 4-L pots. Soil pH in the larger pots was also lower at 0-5 cm depth than at 5-10 cm depth and lower on the edge of the wetting front than directly under the drip emitter. The results indicate that So fertigation is an effective method for quickly reducing soil pH with much less So than conventional application and warrants further investigation in the field.